Genome-Wide Association Study of Seed Quality and Yield Traits in a Soybean Collection from Southeast Kazakhstan - Botakoz Doszhanova; Alibek Zatybekov; Svetlana Didorenko; Chao Fang; Saule Abugalieva; Yerlan Turuspekov (Agronomy)
Soybean (Glycine max (L.) Merr.) is a vital agricultural crop and a key source of protein and oil for food and feed production. The search for new genetic factors affecting the main agronomic traits of soybean is a significant step for efficient breeding strategies. This study aimed to identify marker–trait associations (MTAs) for seed protein and oil content and yield by conducting a genome-wide association study (GWAS). The collection of 252 soybean accessions of five different origins was analyzed over a period of five years. The GWAS was conducted using 44,385 SNP markers extracted from whole-genome resequencing data using Illumina HiSeq X Ten. The multiple-locus mixed linear model (MLMM) facilitated the identification of 38 stable MTAs: nine for protein content, nine for oil content, seven for the number of fertile nodes, six for the number of seeds per plant, four for thousand seeds weight, and three for yield per plant. Fifteen of these MTAs are presumed to be novel, with one linked to seed protein content, three linked to seed oil content, and the remaining MTAs linked to yield-related traits. These findings offer valuable insights for soybean breeding programs aimed at developing new, competitive cultivars with improved seed quality and yield characteristics.